Dimensional Evaluation of Cognitive Measures: Methodological Confounds and Theoretical Concerns. (February 2021) - Decker, Scott L.; Bridges, Rachel M.; Luedke, Jessica C.; Eason, Michael J.
The current study provides a methodological review of studies supporting a general factor of intelligence as the primary model for contemporary measures of cognitive abilities. A further evaluation is provided by an empirical evaluation that compares statistical estimates using different approaches in a large sample of children (ages 9–13 years, N = 780) administered a comprehensive battery of cognitive measures. Results from this study demonstrate the ramifications of using the bifactor and Schmid–Leiman (BF/SL) technique and suggest that using BF/SL methods limit interpretation of cognitive abilities to only a general factor. The inadvertent use of BF/SL methods is demonstrated to impact both model dimensionality and variance estimates for specific measures. As demonstrated in this study, conclusions from both exploratory and confirmatory studies using BF/SL methods are significantly questioned, especially for studies with a questionable theoretical basis. Guidelines for the interpretation of cognitive test scores in applied practice are discussed.